The Mitochondria-to-Cytosol H2O2 Gradient Is Caused by Peroxiredoxin-Dependent Cytosolic Scavenging - Laura de Cubas; Valeriy V. Pak; Vsevolod V. Belousov; José Ayté; Elena Hidalgo (MDPI AG, 2021)
Fluorescent protein-based reporters used to measure intracellular H2O2 were developed to overcome the limitations of small permeable dyes. The two major families of genetically encoded redox reporters are the reduction-oxidation sensitive green fluorescent protein (roGFP)-based proteins fused to peroxiredoxins and HyPer and derivatives. We have used the most sensitive probes of each family, roGFP2-Tpx1.C169S and HyPer7, to monitor steady-state and fluctuating levels of peroxides in fission yeast. While both are able to monitor the nanomolar fluctuations of intracellular H2O2, the former is two-five times more sensitive than HyPer7, and roGFP2-Tpx1.C169S is partially oxidized in the cytosol of wild-type cells while HyPer7 is fully reduced. We have successfully expressed HyPer7 in the mitochondrial matrix, and it is ~40% oxidized, suggesting higher steady-state levels of peroxides, in the low micromolar range, than in the cytosol. Cytosolic HyPer7 can detect negligible H2O2 in the cytosol from mitochondrial origin unless the main H2O2 scavenger, the cytosolic peroxiredoxin Tpx1, is absent, while mitochondrial HyPer7 is oxidized to the same extent in wild-type and ∆tpx1 cells. We conclude that there is a bidirectional flux of H2O2 across the matrix and the cytosol, but Tpx1 rapidly and efficiently scavenges mitochondrial-generated peroxides and stops their steady-state cytosolic levels rising.